Targeting Replication Fork Processing Synergizes with PARP Inhibition to Potentiate Lethality in Homologous Recombination Proficient Ovarian Cancers - Ganesh Pai Bellare; Kshama Kundu; Papiya Dey; Krupa Thankam Philip; Nitish Chauhan; Muskan Sharma; Sankarsingh Kesharsingh Rajput; Birija Sankar Patro (Advanced Science)
Abstract Synthetic lethality in homologous recombination (HR)‐deficient cancers caused by Poly (ADP‐ribose) polymerase inhibitors (PARPi) has been classically attributed to its role in DNA repair. The mode of action of PARPi and resistance thereof are now believed to be predominantly replication associated. Therefore, effective combinatorial approaches of targeting replication fork processing along with HR‐downregulation to target HR‐proficient and possibly PARPi‐resistant tumors are warranted. Stilbenes are a privileged class of molecules, which include resveratrol, pterostilbene, piceatannol, etc, that modulate both replication processes and RAD51‐expression. In this investigation, by screening a small library of stilbenes, including in‐house synthesized molecules, trans‐4,4′‐dihydroxystilbene (DHS) was discovered as a potent natural agent, which downregulates RAD51 expression and HR repair (GFP‐reporter assay). DHS induces extensive synergistic cell death in ovarian cancers when combined with talazoparib (PARPi). Mechanistically, DHS elicits replication‐stress through severely impeding replication fork progress, speed, and inducing fork‐asymmetry. This leads to robust induction of single stranded DNA (ssDNA) gaps and poly‐ADP‐ribosylation (PARylation) in S‐phase cells, signifying issues related to lagging (Okazaki) strand synthesis. PARPi, which abrogates PARylation, potentiates DHS induced ssDNA gaps, and their conversion into lethal double strand breaks through MRE11 action. Furthermore, the combination is highly effective in mitigating ovarian tumor xenograft growth in SCID mice and exhibited a good therapeutic‐index with no/minimal tissue‐toxicity.